Management of pneumonia in intensive care - Morris, Andrew Conway (Journal of Emergency and Critical Care Medicine; Vol 2 (December 2018): Journal of Emergency and Critical Care Medicine, 2018)
Pneumonia, an inflammatory infiltrate of the alveolar airspace, is commonly triggered by bacterial infection of the lungs, or less commonly by viral or fungal infection. It remains the commonest infective reason for admission to intensive care as well as being the most common secondary infection acquired whilst in the intensive care unit (ICU). It presents a significant global burden of disease and is especially prevalent in low- and middle-income countries. The major categories of pneumonia encountered by the Intensive Care clinician are community-acquired, ventilator-acquired, non-ventilator hospital-acquired and pneumonia in the immunocompromised patient. An appreciation of the type of pneumonia a patient has developed is critical to its effective treatment. Pneumonia is the commonest precipitant of acute respiratory distress syndrome (ARDS) and clinicians should be mindful that the evidence-base surrounding ARDS will, in large part, apply to severe pneumonia. The causative organisms which lead to pneumonia vary depending on the site of acquisition (community or hospital-acquired), the immune status of the patient and the presence of intercurrent medications including antibiotics. Current standard microbiological testing is seldom able to give a rapid answer as to which microorganisms is present and causing infection. Therefore, empirical therapy guided by knowledge of local microbial flora and resistance patterns is the recommended course of action. This approach risks the over-treatment of pneumonia with unnecessarily broad-spectrum agents which bring with them the problems of antibiotic-associated harm. Novel rapid diagnostic tests aimed at both the pathogen and the host response hold promise in the rationalisation and appropriate targeting of antimicrobial therapy. At present neither scoring systems nor diagnostic tests are able to accurately risk stratify a patient’s need for intensive care admission. Beyond antibiotic therapy, a number of adjuvant therapies have been trialled in pneumonia although none have yet made it into widespread clinical use. Corticosteroids are recommended in some cases of community-acquired pneumonia (CAP), but their role in the patient with severe CAP in ICU remains uncertain whilst they are a risk factor for the development of hospital and ventilator-acquired pneumonia. Immuno-stimulation has not yet translated from small scale clinical trials into clinical use. Supportive management includes lung protective ventilation, and those interventions proven to improve outcomes in ARDS. This review will give an overview of the epidemiology of severe pneumonia, the microbiological causes and diagnostic strategies. It will then turn to management, including antimicrobial therapy, role of adjuvant therapies, respiratory support and prevention of complications.